Farmer’s Participation in FPO Ecosystem in Eastern Dry Zone of Karnataka - R, Shalini; Ganesamoorthi , Dr. S.; Nagesha , Dr. G.; Siddayya , Dr.; M, Vimala (Electronic Journal of Business and Management, 2023)
The study was conducted in Bangalore Rural and Chikkaballapur district of Karnataka in the year 2022-23 to study the extent of member’s participation in FPO activities. Five FPOs were selected from each district. From each FPO, 10 members were selected. Thus, making a total sample size of a hundred. The participation of members in the FPOs was measured under three main activities viz. functional activities, capacity-building activities and market-oriented activities. The findings of the study revealed that 48.00 % of the FPO members had a moderate level of participation followed by poor (28.00 %) and better (22.00 %) levels of participation in functional activities of FPO. In the case of capacity-building activities, 54.00 % of the FPO members had a moderate level of participation followed by poor (24.00 %) and better (22.00 %) levels of participation. Under marketing activities, 42.00 % of the FPO members had a poor level of participation followed by moderate (39.00 %) and better (19.00%) levels of participation. The results of the overall participation of the members show that more than twofifths (47.00%) of the members belonged to moderate followed by poor (31.00 %) and better (22.00 %) levels of overall participation